Biperiodical bunching system based on the evanescent waves - Ayzatsky, M.I.; Kramarenko, K.Yu.; Perezhogin, S.A. (Вопросы атомной науки и техники, 2001)
To improve the beam bunching at the initial stage of acceleration it is necessary to create an increasing field distribution. Such distribution can be created in a biperiodic disk-loaded waveguide. It is well known that in periodic structures there are two different types of electromagnetic oscillations. In the passbands they exist in the form of travelling waves. In the stopbands electromagnetic oscillations exist in the form of evanescent waves and have the decreasing (increasing) dependence on the coordinate. The properties of electromagnetic oscillations in the stopband that exists in the biperiodic structure due to its biperiodicity are investigated. The results of the simulation of bunching process in the system based on the evanescent wave are presented.